Penerapan Model Kesuksesan Sistem Informasi HOT-Fit terhadap Penggunaan e-Belajar sebagai Media Pembelajaran Daring Berbasis Website (Studi Kasus: STIKI) - Purnomo, Dedy Ari (Jurnal Teknologi dan Manajemen Informatika, 2023)
This research aims to gather the necessary information to build a conceptual model that will be used to measure the success of online learning implemented in higher education institutions. The methodology used in this study is a literature review conducted by comparing various sources such as scientific journals, books, and expert opinions to support the findings. This research employs a quantitative method, where data can be interpreted using statistical analysis, making the quantitative approach more objective, scientific, and rational. The conclusion of this research is a conceptual model that implements the relationship between system quality, service quality, system usage, and user satisfaction with the benefits of e-learning. Furthermore, future related studies can refer to this conceptual model in their implementation.